Integrating the three-line environmental governance and environmental sustainability evaluation of urban industry in China. (10th August 2020) - Cheng, Runhe; Li, Wei; Lu, Zhouyangfan; Zhou, Siyang; Meng, Chong
Abstract: Rapid industrial growth has significantly contributed to the prosperity of Chinese cities over the past decades. Current studies on environmental sustainability (ES) focused on industrial systems, which are the main source of pollution emission, water use, and energy consumption in cities. In light of the weakness of conventional methods in correlating relevant environmental management with ES evaluation, a methodology was developed primarily to improve the evaluation indicators and procedure by integrating the latest three-line environmental governance (TLEG) policy and the ES evaluation of urban industry in China. Specifically, a four-dimensional indicator system was built in a hierarchical structure based on the requirements of TLEG on aspects of ecology, environment, and resource; further, a problem-solving procedure was developed to continuously determine the progress of the industrial ES of the Nansha industrial base (NSIB) in Guangzhou, China. An ad hoc retrospective evaluation was developed to investigate the variations of ES performance of the NSIB from 2005 to 2017 and further to identify a set of restraining indicators exhibiting negative effects on ES. Five alternatives of the industrial upgrading plan up to 2025 were assessed based on the accessibility of ES targets, and the best one was selected against the restraining indicators. The results indicated that the general trend of ES of NSIB was progressive from 2005 to 2017, 13 restraining indicators out of 33 were deemed as key, and Alternative IV was screened out as the best one. This study indicated that such integration with environmental management policies may set up a goal-oriented, problem-solving process for ES evaluation. Further, it may increase the potential to deliver more relevant information for decision-making on the greening industrial systems of cities. Graphical abstract: Image 1 Highlights: Greening industrial system is crucial to sustainable development of Chinese cities. The indicators and procedure are improved by linking the policy with ES evaluation. A restraining indicator set is obtained through a retrospective ES evaluation. The three-line based ES evaluation is a goal-oriented, problem-solving process. Industrial upgrading alternatives are evaluated by accessibility of the ES targets.